Faults in consumer products are difficult to diagnose, and design is to blame: A user observation study. (15th October 2021) - Pozo Arcos, Beatriz; Dangal, Sagar; Bakker, Conny; Faludi, Jeremy; Balkenende, Ruud
Abstract: The process of fault diagnosis is an essential first step when repairing a product: it determines the condition of the parts and identifies the origin of failure. We report on how product users go through the process of fault diagnosis in consumer products and the influence of design features on this process. Two groups of 12 participants were asked to determine the fault in a defective product we supplied; the groups differed in their self-reported repair expertise. Four types of products were used for the study: a vacuum cleaner, kitchen blender, radio CD player, and coffee maker. During the experiment, the participants were asked to think aloud to explain their actions and understandings. Afterwards, they were interviewed regarding their experience. The results from the verbal and video analysis provided input for an updated framework of the diagnosis process, describing user actions at each diagnosis stage. Furthermore, we show that the way a product is designed and constructed (the positioning, accessibility, and visibility of relevant product components) has a significant influence on the success of the fault diagnosis. An important factor is user experience: product use facilitates signal recognition, while repair expertise facilitates disassembly. However, user experience is still less influential than the product's design. Based on these findings, we propose a set of design guidelines to facilitate the process of fault diagnosis in consumer products. Highlights: The product's design is the most relevant factor for fault diagnosis. Component accessibility, visibility, and feedback to the user facilitate diagnosis. The product's design commonly does not offer guidance for the fault diagnosis process. Repair experience facilitates product disassembly. Disassembly hinders the location and isolation of faults.